Monetary Sovereignty and Central Bank Digital Currency - Horváth, Gábor (Public Finance Quarterly, 2022)
The effective monetary sovereignty of a state is the ability of the state to use monetary instruments to achieve its economic policy objectives. This notion goes beyond the conceptualisation of the traditional Westphalian sovereignty of interference-free discretion, which is necessary because of the hierarchical operational complexity of the fiat and credit money systems in the modern financial system. At the same time, the monetary challenges of the 21st century may also erode the effective monetary sovereignty of states, which can, however, be partially rescued through the introduction of digital central bank money. The paper therefore explores different areas of the impact of digital central bank money on effective monetary sovereignty, taking chartalist monetary theory as a starting point. It shows how central bank digital currency may achieve an improvement in these areas of effective monetary sovereignty.